Teacher Empowerment in Child-Friendly Collaborative Learning in Surakarta Elementary Schools - Novitasari, Meggy; Nisa', Choirun; Pramono, Suwito Eko; Heshinta, Linda (Universitas Negeri Makassar, 2025)
ABSTRACTThis Community Service Program (PKM) aims to increase awareness of child-friendly collaborative learning management with programs that refer to strengthening competencies and social emotions that are appropriate to children's developmental needs. The methods used in the community service program include 2 activities, namely guidance activities and mentoring activities. The mentoring activity provides 2 stages of activities, stage I training to improve teacher competency in the social emotional field, stage II training to increase awareness of learning management, while the mentoring activity includes teacher learning clinics and real action activities in the classroom.The results of the community service program in mentoring activities stated that social emotional had a significant impact on the child-friendly learning process, while mentoring activities showed that 71% of teachers were interested in the teacher learning clinic program and 21% of teachers were committed to empowering learning management by compiling teaching modules so that they had an impact on collaborative learning. This means that the activities carried out in the community service program have an impact on cultivating teachers in collaborative, child-friendly learning at Surakarta Elementary Schools.